From Girl to Laurel Tree (or How to Become a Tree): Daphne by Richard Strauss and Joseph Gregor - Díaz Gito, Manuel Antonio (Amaltea. Journal of Myth Criticism, 2017)
Second part of a two-section article that analyses the extensive reinterpretation of Daphne’s myth in the opera Daphne (1938) by composer Richard Strauss and librettist Joseph Gregor, who used the version of the myth by Parthenius of Nicaea better than that by Ovid. Its ultimate aim is to examine Strauss’ statement about his new opera’s meaning and if the authors managed to achieve their objective by means of manipulating the mythical storyline.